Application of the Cox Proportional Hazards Model in Survival Analysis of Hypertensive Patients - Ineu Sulistiana; Zamziri; Ummi Maktum (Inferensi, 2026)
Hypertension is a global health problem and one of the leading causes of mortality in Indonesia, including the Bangka Belitung Islands Province. This study aims to analyze the factors affecting the time required for blood pressure to return to normal in hospitalized hypertension patients at Bakti Timah Hospital Pangkalpinang. The methods used were survival analysis with Kaplan–Meier estimation, the Log-rank test, and the Cox Proportional Hazard Model. The results of the Log-rank test showed that the survival functions of hypertensive patients aged less than 50 years and those aged more than 50 years were statistically significantly different, indicating a different effect on the time to blood pressure normalization. Similarly, the comparison of the survival functions between patients with comorbidities and those without comorbidities showed a statistically significant difference, indicating a different effect on the time to blood pressure normalization among hypertensive patients. The best model obtained was h_i (t│X)=h_o (t)exp⁡(〖-2,82047〗_(hypertensive patients with comorbidities)). Based on the Hazard Ratio (HR), hypertensive patients with comorbidities have a hazard of achieving normal blood pressure that is 0.06 times that of hypertensive patients without comorbidities.